Foreground-Background Separation by Feed-forward Neural Networks in Old Manuscripts - Kefali, Abderrahmane; Sari, Toufik; Bahi, Halima (Informatica, 2014)
Artificial Neural Networks (ANNs) are widely used techniques in image processing and patternrecognition. Despite of their power in classification tasks, for pattern recognition, they show limitedapplicability in the earlier stages such as the foreground-background separation (FBS). In this paper anovel FBS technique based on ANN is applied on old documents with a variety of degradations. Theidea is to train the ANN on a set of pairs of original images and their respective ideal black and whiteones relying on global and local information. We ran several experiments on benchmark and syntheticdata and we obtained better results than state-of-the art methods.